2020
DOI: 10.1051/matecconf/202032111027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different titanium alloys welded by Yb:YAG fibre laser for thin sheet applications used for T-ducts in bleed air systems

Abstract: Research in aerospace applications includes the replacement of well-known materials by newly developed alloys or by new manufacturing methods for the existing materials. In the frame of TiB-Air project funded by the German Federal Ministry for Economic Affairs and Energy (BMWi) the development of a process chain consisting of deep drawing at elevated temperatures, chemical milling, contour machining by laser cutting and laser beam welding to produce pneumatic T-ducts used in bleed air systems is in focus. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is commonly applied in exhaust and tube systems. In [5] it was shown that the alloy has well-balanced properties in terms of mechanical strength, fatigue strength and fracture resistance, therefore the alloy is valuable for industry and can replace conventional titanium alloys such as Ti Grade 2 and Ti Grade 4. Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly applied in exhaust and tube systems. In [5] it was shown that the alloy has well-balanced properties in terms of mechanical strength, fatigue strength and fracture resistance, therefore the alloy is valuable for industry and can replace conventional titanium alloys such as Ti Grade 2 and Ti Grade 4. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The Ti KS1.2ASN alloy studied in this work has not attracted much attention from researchers until recently. However, it has promising properties in terms of mechanical and fatigue strength as well as fracture resistance [5]. Nawaya et al [6] studied the tensile properties of α-titanium alloys (including Ti KS1.2ASN) at elevated temperatures and it was observed that the alloys reach the maximum formability in a certain temperature range (in the paper it was approx.…”
Section: Introductionmentioning
confidence: 99%